(untitled) (International Seven Journal of Health Research, 2024)
Introduction: Colorectal cancer (CRC) is the third most frequent type of cancer in the world in both sexes, starting in the large intestine and extending to the lower part of the digestive system. However, complications such as abscess formation, bleeding, perforation, and obstruction arise in some patients with colon cancer. The most important risk factor is family history of CRC and genetic predisposition to the development of chronic bowel diseases, as well as diet, excessive alcohol consumption, and smoking. When identified early, it is a pathology that has a good prognosis, so the importance of colonoscopy as a screening test is evident. Objective: to demonstrate the importance of tests to identify colon cancer early to improve a prognosis and avoid possible complications. Methods: From a medical case that occurred at the Santa Casa da Misericórdia de Presidente Prudente, and its medical records, information was collected to carry out this report. Results: RCC is characterized by the appearance of metastases. In addition, this type of neoplasm occurs more commonly in the elderly, as in the case of the patient in this study. The medical approach depends on the joint evaluation of the clinical-laboratory-radiological picture presented by the patient, and its treatment varies according to the staging. Conclusion: The treatment of RCC varies between endoscopic resection of malignant polyps, surgery alone, and surgery associated with chemotherapy. Therefore, identifying the disease as early as possible significantly increases the chances of cure, along with proper treatment and follow-up.